Head and Neck Cancer: Underfunded and Understudied?. (January 2017) - Svider, Peter F.; Blasco, Michael A.; Raza, S. Naweed; Shkoukani, Mahdi; Sukari, Ammar; Yoo, George H.; Folbe, Adam J.; Lin, Ho-Sheng; Fribley, Andrew M.
Despite a considerable expansion in our therapeutic repertoire for management of other malignancies, mortality from head and neck cancer (HNC) has not significantly improved in recent decades. Upon normalizing National Institutes of Health–awarded R01 and R01-equivalent grants by incidence, thyroid cancer (214) and HNC (1329) received the fewest funding dollars. Upon adjusting funding totals by mortality, HNC was 7th out of 9 cancers evaluated (6138). These findings highlight HNC as an underfunded disease versus other cancers. As data detailing grant applications (including unsuccessful grants) are not publicly available, it is not clear if these disparities stem from fewer applications or fewer opportunities. Our hope is that this commentary will spur further investigation into strategies to increase HNC inquiry and funding for trainees as well as early-stage and established investigators.